Filtering Out Use of DOACs in Hemodialysis. (June 2017) - Dager, William E.; Lee, Jin A.
Published data exploring the best approach to initiating and maintaining anticoagulation in the setting of renal support therapy are scarce, as these patients were excluded in clinical trials. When developing an anticoagulation regimen in this setting, it is important to assess thrombosis risk, identify the unique drivers for thrombosis and bleeding, and recognize the limitations of supporting evidence behind approved prescribing indications for renal impairment. Available literature and considerations for using direct acting oral anticoagulants in the setting of renal support are reviewed.